PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP KINERJA PADA KARYAWAN PT. INKA MULTI SOLUSI (IMS) MADIUN - Raihan Fadhil Hakim Musyaffa; Lukman Hakim (POLITEKNIK LP3I JAKARTA, 2024)
The purpose of this study was to analyze the effect of job satisfaction and job stress on performance in employees of PT Inka Multi Solusi (IMS) Madiun. This research method uses a quantitative approach. This research uses primary data sources. Primary data was collected using a questionnaire. The population in this study were all employees who worked at PT.IMS Madiun, totaling 2540 people. The sampling technique used purposive sampling with certain criteria. Based on Malhotra's calculation, the sample used was 82 respondents. The data analysis methods used in this study are validity, reliability, and research instrument tests. SPSS software was used to analyze the research data. The results of this study are that job satisfaction, job stress can affect employee performance. Job satisfaction, job stress simultaneously have a significant impact on employee performance. If job satisfaction increases by 1 unit, employee performance is expected to increase by 0.557. In addition, it is known that the regression coefficient for the work stress variable is 0.206, which is positive. This indicates that when job stress increases by 1 unit, employee performance also tends to increase by 0.206.